2017
DOI: 10.1007/s00018-017-2651-5
|View full text |Cite
|
Sign up to set email alerts
|

Periostin in vitreoretinal diseases

Abstract: Proliferative vitreoretinal diseases such as diabetic retinopathy, proliferative vitreoretinopathy (PVR), and age-related macular degeneration are a leading cause of decreased vision and blindness in developed countries. In these diseases, retinal fibro(vascular) membrane (FVM) formation above and beneath the retina plays an important role. Gene expression profiling of human FVMs revealed significant upregulation of periostin. Subsequent analyses demonstrated increased periostin expression in the vitreous of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Periostin (POSTN) is a Fasciclin family stromal cell protein [ 25 ] that is believed to initiate cell proliferation, migration and epithelial-to-mesenchymal transformation by interacting with several integrins, including αVβ3, αVβ5 and α6β4 [ 26 , 27 ]. Our study found POSTN to be significantly expressed in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin (POSTN) is a Fasciclin family stromal cell protein [ 25 ] that is believed to initiate cell proliferation, migration and epithelial-to-mesenchymal transformation by interacting with several integrins, including αVβ3, αVβ5 and α6β4 [ 26 , 27 ]. Our study found POSTN to be significantly expressed in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Its highest expression, however, is found in ERMs associated with PDR. Similar to osteonectin, periostin has been shown within ERM cells [ 56 ]. Proteomic profiling did not detect thus protein in iERMs [ 13 ].…”
Section: Ecm Components Of Iermsmentioning
confidence: 99%
“…24 The development of PVR subretinal and epiretinal membranes is associated with vitreal accumulation of inflammatory cells, 25 including a significant elevation CD163/CD206expressing M2 macrophages. [26][27][28] Microglia, which regulate macrophage infiltration, proliferate and infiltrate through the retina and into the subretinal space within days of detachment. 29,30 peritoneal macrophages injected into the vitreous of the rabbit trans-differentiate into fibroblast-like cells and initiate intraretinal fibrosis similar to that seen in PVR.…”
Section: Inflammatory Phasementioning
confidence: 99%
“…Periostin is a fibroblast-derived matricellular mitogenic protein that stimulates EMT in cancer cells, accelerates cutaneous wound healing by activating fibroblasts 184,185 and causes inflammatory chemotaxis of TH2 cells and M2 macrophages by inducing cytokine production. 186,187 In patients with PVR, vitreal periostin levels are elevated along with high periostin expression in PVR membranes, 27 and the protein is produced in vitro by RPE cells that undergo TGFβ 2 -induced EMT. 106 These findings provide little support that periostin is likely to be useful as a predictive PVR molecular biomarker.…”
Section: Periostinmentioning
confidence: 99%